FIGURE 27 in Taxonomy, ecology and zoogeography of the Recent species of Rhamphostomella Lorenz, 1886 and Mixtoscutella n. gen. (Bryozoa, Cheilostomata) - Grischenko, Andrei V.; Gordon, Dennis P.; Taylor, Paul D.; Kuklinski, Piotr; Denisenko, Nina V.; Spencer-Jones, Mary E.; Ostrovsky, Andrew N. (Zenodo, 2022)
FIGURE 27. Mixtoscutella ovata (Smitt, 1868). ZIRAS 36/50120 (western Kamchatka, Sea of Okhotsk). A. Colony margin with young and developing zooids (arrows, sites of ooecial development). B. Zooidal orifice, showing condyles, and suboral avicularium. C, D. Non-ovicellate zooids in young part of colony. E. Ovicellate zooids in older part of colony, showing ovicells, and suboral and adventitious avicularia. F. Ooecium covered by secondary calcification, except in proximal triangular area with pseudopores. G. Area of colony with ovicellate zooids and adventitious avicularia. H. Longitudinal section through frontal shield, showing interior of umbonulomorph suboral area and adjacent pseudoporous lepralioid shield. I. Interior of frontal shield with umbonuloid component, ring scar, areolae (smaller lateral openings in upper part of zooid), pseudopores and ooecial pore (arrow). J. Internal view of primary orifice with condyles. K. Basal surface of colony. L. Interior of frontal shield, showing blurred ring scar and exterior wall microstructure of umbonuloid component. M. Lateral view of zooid, showing frontal shield, suboral avicularium and lateral wall with mural pore chambers. Scale bars: A, D, G, K, 500 μm; B, F, I, J, 100 μm; C, E, 250 μm; H, L, 50 μm; M, 200 μm. Published as part of Grischenko, Andrei V., Gordon, Dennis P., Taylor, Paul D., Kuklinski, Piotr, Denisenko, Nina V., Spencer-Jones, Mary E. & Ostrovsky, Andrew N., 2022, Taxonomy, ecology and zoogeography of the Recent species of Rhamphostomella Lorenz, 1886 and Mixtoscutella n. gen. (Bryozoa, Cheilostomata), pp. 1-115 in Zootaxa 5131 (1) on page 84, DOI:10.11646/zootaxa.5131.1.1, http://zenodo.org/record/6521113